Taller de reflexión: Enfoques teóricos y perspectivas metodológicas en los estudios de las familias y las movilidades - Guerra, Germán; Szasz, Ivonne (El Colegio de México A.C., 2013)
On June 11, 2010 at El Colegio de México, a workshop for reflection was conducted on Theoretical and Methodological Perspectives in Studies on Families and Mobilities. This workshop, motivated by the intellectual effort of several researchers affiliated to various academic institutions, focused on reflections on migration, both internal and international, urban and rural, intra-urban mobility and family arrangements: composition and intergenerational relations, changing roles, support networks, child and elder care arrangements and gender relations.This paper summarizes the presentations by the scholars and researchers who contributed to the workshop, in conjunction with the discussions raised by these presentations among the attendees. In addition to concentrating these theoretical, critical and methodological reflections and sharing them with the interested public, the report aims to raise the need to form a group of theoretical-methodological reflection to study relations between families and migration as interrelated fields of study.